Research Data Management at UiT: An introduction ... - UiT The Arctic University Of Norway (Zenodo, 2022)
Course material for the webinar “Research Data Management at UiT: An introduction”, part of a webinar series on research data management (RDM) organized by UiT The Arctic University of Norway. For more information, please visit: site.uit.no/rdmtraining ...